Improving signal quality of a speech codec using hybrid perceptual-parametric algorithm. (26th September 2008) - Kulesza, Maciej; Szwoch, Grzegorz; Czyzewski, Andrzej
A hybrid parametric-perceptual speech codec architecture is presented. The basic CELP parametric codec structure is enhanced using the perceptual coding method. The objective of the codec hybridisation is obtaining significant improvement in the perceived signal quality. Two hybrid architectures are proposed. The first one encodes voiced parts perceptually in the CELP residual signal. The second one divides the signal into voiced signal components that are encoded using the perceptual algorithm, unvoiced components that are encoded parametrically and transients remaining unencoded. The signal quality achieved using the hybrid codec is compared to the quality of some standard speech codecs.